Predictive Factors for Additional Non-Sentinel Lymph Node Involvement in Breast Cancer Patients with One Positive Sentinel Node. Issue 1 (January 2015) - Meattini, Icro; Saieva, Calogero; Bertocci, Silvia; Francolini, Giulio; Zei, Giacomo; De Luca Cardillo, Carla; Scotti, Vieri; Greto, Daniela; Bonomo, Pierluigi; Orzalesi, Lorenzo; Bianchi, Simonetta; Livi, Lorenzo
Aim: The aim of this study was to identify a subgroup of breast cancer patients in whom it is possible to avoid axillary lymph node dissection (ALND) when the sentinel lymph node (SLN) is positive. Methods: A series of 292 patients treated with breast-conserving surgery or mastectomy underwent ALND after positive SLN detection. To correlate SLN metastasis with the chances of finding additional metastasis in non-SLNs we evaluated the main clinicopathological characteristics. No patients received adjuvant radiotherapy to the axillary region. Results: Fifty-six patients (35.4%) with positive SLNs for macrometastases (n = 158) had additional metastases upon completion ALND compared with 7 patients (5.2%) with micrometastases in the SLN (n = 132). Cases with a higher number of positive axillary lymph nodes tended to have higher pT stage (p = 0.004). In multivariate analysis, pT was confirmed as an independent predictor of non-SLN metastases (OR = 2.40; 95% CI = 1.16-4.99). No patients with micrometastases in SLN and cancer <10 mm had additional positive non-SLNs. Conclusions: Our results, in agreement with the major published studies, suggest that ALND can be avoided in selected patients without the need for additional treatment to the axillary region.